User Modeling 2007 11th International Conference, UM 2007, Corfu, Greece, July 25-29, 2007. Proceedings - Conati, Cristina; McCoy, Kathleen; Paliouras, Georgios; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
As the variety and complexity of interactive systems increase, understanding how a system can dynamically capture relevant user needs and traits, and - tomatically adapting its interaction to this information, has become critical for devising e?ective advanced services and interfaces. The International User M- eling Conference represents the central forum for presenting the advances in the research and development of personalized, user-adaptive systems. Bi-annual scienti?c meetings of the user modeling community started in 1986 as a small invitational workshop held in Maria Laach, Germany, with 24 participants. The workshops continued with an open format, and grew into an international c- ference with 74 submissions in 1994. While maintaining its feel as a highly - gaged and intimate community, the conference has continued to grow, reaching the record number of 169 submissions (153 full papers and 16 posters) in this current edition, held in Corfu, Greece. With an acceptance rate of 19. 6% for long papers and 38% for posters, - lected by a team of reviewers who proved to be exceptionally thorough and thoughtful in their reviewers, this year$1 (Bs program followed the high standards set by the previous editions, and presented an exciting range of interdisciplinary work covering topics such as cognitive modeling, modeling of user a?ect and meta-cognition,empirical evaluations of noveltechniques, user modeling for - bilecomputingandrecommendersystems,useradaptivityandusability.s
Invited Papers -- The Disappearing Computer: User-Centered Interaction Design for Smart Artefacts -- Experience Medium: Toward a New Medium for Exchanging Experiences -- Intelligent Assistive Technology: The Present and the Future -- Full Papers -- Exploiting Evidence Analysis in Plan Recognition -- Modeling the Acquisition of Fluent Skill in Educational Action Games -- A User Modeling Server for Contemporary Adaptive Hypermedia: An Evaluation of the Push Approach to Evidence Propagation -- Principles of Lifelong Learning for Predictive User Modeling -- Users in Volatile Communities: Studying Active Participation and Community Evolution -- Learning from What Others Know: Privacy Preserving Cross System Personalization -- Construction of Ontology-Based User Model for Web Personalization -- Preference-Based Organization Interfaces: Aiding User Critiques in Recommender Systems -- (3z(BMore Like This(3y (Bor (3z(BNot for Me(3y(B: Delivering Personalised Recommendations in Multi-user Environments -- Feature-Weighted User Model for Recommender Systems -- Evaluating a Simulated Student Using Real Students Data for Training and Testing -- Modeling Students$1 (BNatural Language Explanations -- Applications for Cognitive User Modeling -- Identifiability: A Fundamental Problem of Student Modeling -- Understanding the Utility of Rationale in a Mixed-Initiative System for GUI Customization -- Respecting Users$1 (BIndividual Privacy Constraints in Web Personalization -- Personalized Previews of Alternative Routes in Virtual Environments -- Visual Attention in Open Learner Model Presentations: An Eye-Tracking Investigation -- EEG-Related Changes in Cognitive Workload, Engagement and Distraction as Students Acquire Problem Solving Skills -- Eliciting Motivation Knowledge from Log Files Towards Motivation Diagnosis for Adaptive Systems -- Assessing Learner$1 (Bs Scientific Inquiry Skills Across Time: A Dynamic Bayesian Network Approach -- From Modelling Domain Knowledge to Metacognitive Skills: Extending a Constraint-Based Tutoring System to Support Collaboration -- Mobile Opportunistic Planning: Methods and Models -- Analyzing Museum Visitors$1 (BBehavior Patterns -- A Context-Aware Movie Preference Model Using a Bayesian Network for Recommendation and Promotion -- Intrinsic Motivational Factors for the Intention to Use Adaptive Technology: Validation of a Causal Model -- Improving Social Filtering Techniques Through WordNet-Based User Profiles -- Push-Poll Recommender System: Supporting Word of Mouth -- Evaluation of Modeling Music Similarity Perception Via Feature Subset Selection -- Poster Papers -- A Practical Activity Capture Framework for Personal, Lifetime User Modeling -- A Probabilistic Relational Student Model for Virtual Laboratories -- A Semantics-Based Dialogue for Interoperability of User-Adaptive Systems in a Ubiquitous Environment -- A User Independent, Biosignal Based, Emotion Recognition Method -- A User Model of Psycho-physiological Measure of Emotion -- A User-Item Predictive Model for Collaborative Filtering Recommendation -- Automatic Generation of Students$1 (BConceptual Models from Answers in Plain Text -- Capturing User Interests by Both Exploitation and Exploration -- Conceptualizing Student Models for ICALL -- Context-Dependent User Modelling for Smart Homes -- Conversations Amidst Computing: A Study of Interruptions and Recovery of Task Activity -- Cross-Domain Mediation in Collaborative Filtering -- Driver Destination Models -- Enabling Efficient Real Time User Modeling in On-Line Campus -- Eliciting Adaptation Knowledge from On-Line Tutors to Increase Motivation -- Improving User Taught Task Models -- Inducing User Affect Recognition Models for Task-Oriented Environments -- Interactive User Modeling for Personalized Access to Museum Collections: The Rijksmuseum Case Study -- Kansei Processing Agent for Personalizing Retrieval -- Maximizing the Utility of Situated Public Displays -- Modeling Preferences in a Distributed Recommender System -- Multiple Evidence Combination in Web Site Search Based on Users$1 (BAccess Histories -- MyPlace Locator: Flexible Sharing of Location Information -- Personalised Mashups: Opportunities and Challenges for User Modelling -- Personalized Control of Smart Environments -- Studying Model Ambiguity in a Language ITS -- Tailoring and the Efficiency of Information Seeking -- The Effect of Model Granularity on Student Performance Prediction Using Bayesian Networks -- To Share or Not to Share: Supporting the User Decision in Mobile Social Software Applications -- Towards a Tag-Based User Model: How Can User Model Benefit from Tags? -- Web Customer Modeling for Automated Session Prioritization on High Traffic Sites -- What$1 (Bs in a Step? Toward General, Abstract Representations of Tutoring System Log Data -- Doctoral Consortium Papers -- Encouraging Contributions to Online Communities with Personalization and Incentives -- Semantic-Enhanced Personalised Support for Knowledge Sharing in Virtual Communities -- Explaining Recommendations -- Designing Persuasive Health Behaviour Change Dialogs -- User-Centered Design for Personalized Access to Cultural Heritage.s
Keywords: Computer science; User interfaces (Computer systems).; Artificial intelligence; Computer simulation; Application software; Computers and civilization; Computer Science; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Simulation and Modeling; Computers and Society; Computer Appl. in Social and Behavioral Sciences; Electronic books